Relationship of Myopia Degree with Retinal Detachment Incidence at Diponegoro National Hospital - Pradya Rahmawati Subagyo; Trilaksana Nugroho; Arnila Novitasari Saubig (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Myopia is one of the visual disorders that has a high prevalence in the world. Based on the severity degree, myopia is divided into three criteria, namely mild, moderate and severe. Severe-degree myopia patients are more likely to suffer from certain eye diseases, especially those associated with the retina, such as retinal detachment.Objective: To analyze the relationship between the degree of myopia and the incidence of retinal detachment.Methods: This research is an observational analytical with cross-sectional approach. The research data was obtained using consecutive sampling from the medical records of myopia patients in Diponegoro National Hospital during 2015-2020. Research subjects used in this research were 70 patients who fulfill the inclusion and not the exclusion criteria. The data were analyzed using Chi Square test. Results: The prevalence of retinal detachment is dominated by the age group of 51-60 years old (18.6%), male (35.7%) and a severe degree of myopia (34.3%). The results of the Chi Square test show that there is a significant relationship between the severity degree of myopia and the incidence of retinal detachment.Conclusion: There is a significant relationship between the degree of myopia and the incidence of retinal detachment.